Student Responses to Personal Digital Inquiry (PDI) Learning Integrated with Citizen Science Project (CSP) on Biodiversity Materials in a Senior High School - Mahmudah Nur Cahyaningrum; Topik Hidayat; Kusnadi Kusnadi (Research Synergy Foundation, 2025)
The research was motivated by the fact that biodiversity is declining; therefore, the involvement of all parties, including students, is needed to help save biodiversity. One way to do this is to implement meaningful learning by utilizing the closeness of students and gadgets through the application of personal digital inquiry-integrated citizen science projects in the classroom, which involve experts in carrying out biodiversity conservation projects in the form of a